Dearly : new poems - Atwood, Margaret, 1939- (Ecco, an imprint of HarperCollinsPublishers, 2020)
The internationally acclaimed author presents her first collection of poetry in over a decade that addresses themes such as love, loss, the passage of time, nature, and zombies.